Magnetic resonance image degradation from prosthetic magnet keepers - Laurell, Kim A.; Gegauff, Anthony G.; Rosenstiel, Stephen F. (The Journal of prosthetic dentistry, 1989)
Eight types of prosthetic magnet keepers were imaged in a water phantom and a living human subject by a 1.5 T magnetic resonance device. Image artifacts were present for all eight samples and ranged from 160 mm to greater than 280 mm in diameter. These artifacts obliterate vital craniocervical areas making their examination by magnetic resonance impossible. Patients with magnetic keepers requiring comprehensive magnetic resonance imaging of the head and neck region must have them removed.